Globalization and rural poverty: A perspective from a social observatory in the Philippines - Yujiro Hayami (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Using a rice village in the Philippines as a social observatory, the impacts of modernization forces under globalization on rural poverty are assessed based on data collected from recurrent household surveys over the past three decades. After cultivation frontiers closed in the early 1950s relentless population increases continued to press hard on limited land resources in this village. This pauperizing force was counteracted to some extents by the development of irrigation systems followed by the diffusion of modern high-yielding varieties of rice. However, the much more important factor that prevented poverty incidence from increasing and income inequality from worsening was identified as the expansion of non-farm employment opportunities resulting from the increased integration of this village with wide urban and foreign markets. This finding does not lend support to the popular assertion that the encroachment of markets into traditional agrarian communities tends to result in greater inequality and misery of the poor. – globalization ; poverty ; Philippines ; agriculture
Keywords: O33; Q13; Q15; Q16; 330; Ländliche Armut; Dorf; Globalisierung; Philippinen